The Role of Febrile Neutropenia Guideline’s Implementation on Mortality Rate in Dharmais Hospital-National Cancer Center - Ranuhardy, Dody (National Cancer Center - Dharmais Cancer Hospital, 2018)
Introduction: Febrile neutropenia have a high morbidity and mortality impact for the patient. The mortality rate of febrile neutropenia in 2002 was 38.8%, while it was 27.3% in 2009. The difference in mortality rates could be caused by several factors such as availability of the Neutropenic Fever Management Guidelines in 2006, in addition to infrastructure, human resources and equipment. This study aims to determine the role of guideline availibility and other factors to cancer mortality rate in the immunocompromised isolation room of Dharmais Hospital. Methods: This study was a cross-sectional retrospective study which investigate mortality rates and compare with adherence to febrile neutropenia guidelines for the period 2008-2012. Data were taken from the patient's medical record file, and then analysed using univariate and bivariate analysis. Results: The mortality rate in the period 2008-2012 was 20.7%. The correlation between age, sex, and degree of risk factor on mortality was not significantly different (p=0,409, p=0,404, and p=0,324). The proportion of deaths was higher in patients borne by third parties (26.8%) than in the case of personal (10%) although not statistically significant (p=0,065). From the three types of adherence, only one had a significant effect of adherence to treatment flow (p=0,033). Conclusions: The availibility of management guideline can reduce mortality rate of febrile neutropenia even though from the three types of adherence, only one had a significant effect of adherence to treatment flow (p=0,033).